Longitudinal study on periodontal conditions in healthy elderly people in Japan - Hirotomi T, Yoshihara A, Yano M, Ando Y, Miyazaki H (Blackwell Synergy, 2002)
A strategy for the control of periodontal disease progression is required to prevent tooth loss in older people. However, detailed epidemiological data on periodontal conditions in elderly people is limited.